EZH2-mediated H3K27me3 is a predictive biomarker and therapeutic target in uveal melanoma - Hou, Chen; Xiao, Lirong; Ren, Xiang; Cheng, Lin; Guo, Bo; Zhang, Meixia; Yan, Naihong (Frontiers in Genetics, 2022)
Although gene mutations and aberrant chromosomes are associated with the pathogenesis and prognosis of uveal melanoma (UM), potential therapeutic targets still need to be explored. We aim to determine the predictive value and potential therapeutic target of EZH2 in uveal melanoma. Eighty-five uveal melanoma samples were recruited in our study, including 19 metastatic and 66 nonmetastatic samples. qRT-PCR, immunohistochemistry staining, and western blotting were applied to detect the expression of EZH2 and H3K27me3. We found that EZH2 (41/85, 48.24%) and H3K27me3 (49/85, 57.65%) were overexpressed in uveal melanoma. The expression of EZH2 was not significantly associated with metastasis. High H3K27me3 expression was correlated with poor patient prognosis. UNC1999, an EZH2 inhibitor, can downregulate H3K27me3 expression and has the most potency to inhibit OMM1 cell growth by the cell cycle and ferroptosis pathway. These results indicate that H3K27me3 can be a biomarker predicting a poor prognosis of UM. EZH2 is the potential therapeutic target for UM.